PENDUGAAN KEINDAHAN LANSKAP CANDI PANATARAN KABUPATEN BLITAR, JAWA TIMUR - Baptisa, Faustina De Jesus; Budiyono, Debora; Soelistyari, Hesti Trisna (Fakultas Pertanian, 2019)
The Complex temple panataran is one of the largest temples in the province of East Java, located on the slope of Kelud Mountain in Penataran Village, Nglegok District, Blitar Regency. The potential that exists in Panataran temple is as a religious place for the Hindu religious community and as a tourist area that increases the economy of all communities. The current condition of the temple area is in the middle of residential areas and only separated by a fence with a visual landscape as originally planned for the area, settlements, buildings, agricultural land. The purpose of this study was to identify and analyze the visual condition of the landscape at Panataran Temple. The method used in this research is quantitative descriptive while the method for analyzing data is the method SBE (Scenic Beauty Estimation). Based on the results of research that the visual landscape of the Panataran Temple area has three beauty classifications namely beautiful 41.43%, quite beautiful 19.35%, and not beautiful 54.53%. From the results that are known under the classification of beauty that is not beautiful and quite beautiful it is necessary to add facilities, green space and RTB so that in the Panataran Temple area there is comfort, safety and beauty for the local community and visitors. Kompleks Candi Panataran merupakan salah satu Candi terbesar di provinsi Jawa Timur, terletak di lereng gunung Kelud di Desa Penataran, Kecamatan Nglegok, Kabupaten Blitar. Potensi yang ada di Candi Panataran adalah sebagai tempat religi bagi masyarakat agama Hindu beribadah dan sebagai tempat kawasan wisata yang meningkatkan perekonomian bagi semua masyarakat. Kondisi kawasan candi saat ini berada di tengah-tengah pemukiman penduduk dan hanya dipisahkan oleh pagar dengan visual lanskap sebagaimana awal fungsinya yang telah direncanakan pada kawasan, pemukiman, bangunan, dan lahan pertanian.Tujuan dari penelitian ini untuk mengidentifikasi dan menganalisis kondisi visual lanskap pada Candi Panataran. Metode yang digunakan dalam penelitian ini adalah deskriptif kuantitatif sedangkan metode untuk menganalisis data adalah metode SBE (Scenic Beauty Estimation). Berdasarkan hasil penelitian yang bahwa visual lanskap kawasan Candi Panataran memiliki tiga klasifikasi keindahan yaitu indah 41.43%, cukup indah 19.35%, dan tidak indah 54.53%. Dari hasil yang sudah diketahui bawah klasifikasi keindahan yang tidak indah dan cukup indah perlu adanya penambahan fasilitas dan RTH maupun RTB sehingga dalam kawasan Candi Panataran terdapat kenyamanan, keamanan, dan keindahan bagi masyarkat setempat maupun pengunjung.